THE INFLUENCE OF KNOWLEDGE, RELIGIOSITY, AND SOCIAL ENVIRONMENT ON INTEREST IN SAVING IN ISLAMIC BANKING - Hasan, Irmayanti Yanti; Wati, Mirro Faricha (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
Financial institutions have the function of channeling and collecting funds. There are various products to raise funds, one of which is savings products. Each individual has a determining factor in choosing a product to be used or to be purchased, such as factors of knowledge, religiosity, and social environment. This research was conducted in Wates Hamlet which is located in the Sidoarjo Regency, East Java, because the area is a cottage industry area. This study has the aim of identifying the effect of knowledge, religiosity, and social environment on interest in saving in Islamic banks. In this study, 97 respondents were obtained randomly using the solvin formula, where these respondents were residents or people of Dusun Wates. The type of this research is quantitative research that uses multiple linear regression method. The results of the study indicate that the variables of knowledge, religiosity, and social environment have an influence either partially or simultaneously on the interest in saving in Islamic banks which is shown at a significance level of less than 0.05 or 5%.